Folic acid in treatment of wastewater in coffee via wet processing - Teixeira, Denis Leocádio; Matos, Antonio Teixeira; Rossmann, Maike (Coffee Science - ISSN 1984-3909, 2012)
Since Brazil is a major producer of coffee in the world, the waste that it generates should be of great environmental concern. The coffee processing wastewater (CPW) can bring serious environmental impacts if disposed untreated, due to the large amount of macro/micronutrients and phenolic compounds that they have. Folic acid, a vitamin complex essential in metabolic pathways, can stimulate the development of microorganisms in the environment and thereby provide more rapid removal of the organic load of wastewater. The purpose of this work was to evaluate the influence of varying concentrations of folic acid in stimulating the degradation of organic material contained in the CPW and also investigate the effect of solubility of folic acid in distilled water, distilled boiling water, and a solution of sodium bicarbonate. The addition of folic acid in concentrations from 4.0 to 32.0 mg L-1 increased the rate of decay of chemical oxygen demand (COD). The dose of 8 mg L-1 folic acid diluted in distilled water provided the optimum results in terms of removing organic material from the CPW.